On the Unification of Explanations of Terms in the Explanatory Dictionary (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
The article discusses the features of the formation of systematic definitions – typical definitions of socio-political terms in the “explanatory dictionary of the Uzbek language”, positive and negative aspects of the unification of definitions in the dictionary.